Pengelolaan Pesisir Pasca UU Cipta Kerja: Harmonisasi Kewenangan Pusat dan Daerah - Setyawan, Agus; Sinaga, Parbuntian; Bhakti, Teguh Satya (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the authority structure between the Ministry of Maritime Affairs and Fisheries (KKP) and Regional Governments in managing coastal areas through marine spatial utilization following the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. The main instrument studied is the Confirmation of Conformity of Marine Spatial Utilization Activities (KKPRL), which functions as a licensing instrument and a control mechanism to ensure that marine spatial utilization activities remain directed, integrated, and aligned with the principles of ecological, social, and economic sustainability. The research approach used is a juridical-empirical approach with a qualitative descriptive analysis method. Through this approach, the research not only examines legal norms but also captures the practice of implementing authority in the field. The results show that although the Job Creation Law is oriented towards simplifying business licensing, several problems remain that have implications for the effectiveness of coastal governance. These issues include disharmony between central and regional regulations, overlapping authority between the Ministry of Marine Affairs and Fisheries (KKPRL) and regional governments, and weak synchronization between national policies and regional instruments such as the Coastal and Small Islands Zoning Plan (RZWP3K). In addition to regulatory constraints, this study also highlights institutional and technical aspects. Limited human resource capacity in the regions, a lack of understanding of KKPRL procedures, and minimal inter-agency coordination hamper the effectiveness of coastal management. These conditions result in slow investment realization, conflicts over spatial use, and potential coastal environmental degradation. Therefore, this study recommends a strategy for harmonizing authority through improving vertical-horizontal coordination, strengthening the institutional capacity of regional governments, and developing derivative regulations consistent with the principles of good governance.